2013
DOI: 10.1002/jgrd.50568
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐based total ozone column measurements and their diurnal variability

Abstract: [1] Three Brewer spectrophotometers were set up in three tropical sites of South America (in the Bolivian Altiplano and seashore and biomass burning areas of Brazil) to measure the total ozone column (TOC). Only TOC measurements with uncertainties ≤1% (1σ) were considered. Typically, the standard deviation for the diurnal sets of measurements was predominantly ≤1% for two of these sites. The average variability in TOC ranged from 6.3 Dobson units (DU) to 16.8 DU, and the largest variability reached 54.3 DU. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Silva et al . have shown that TOC measurements obtained within a few minutes in Belo Horizonte by a MII have standard deviations up to 4% of the average TOC, and Silva has shown that TOC measurements obtained in Campo Grande (20.44°S, 54.65°W, 532 m a.s.l., 8093 km 2 , Brazil) by a Brewer spectrophotometer can present an average variability of 3% of the daily average TOC. It means the uncertainty in EDR cf caused by the uncertainty of using just one value of TOC per day is practically equal to the correction provided by SRF cf to EDR at SZA < 60° .…”
Section: The Edr Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al . have shown that TOC measurements obtained within a few minutes in Belo Horizonte by a MII have standard deviations up to 4% of the average TOC, and Silva has shown that TOC measurements obtained in Campo Grande (20.44°S, 54.65°W, 532 m a.s.l., 8093 km 2 , Brazil) by a Brewer spectrophotometer can present an average variability of 3% of the daily average TOC. It means the uncertainty in EDR cf caused by the uncertainty of using just one value of TOC per day is practically equal to the correction provided by SRF cf to EDR at SZA < 60° .…”
Section: The Edr Measurementsmentioning
confidence: 99%
“…Since there was neither satellite data nor ground‐based measurement of TOC on DEC292009, the monthly average MII TOC for December 2009 ± 1 standard deviation was adopted as the value of TOC for the day. Despite the diurnal variability of 3–4% in TOC , let's assume that each value of TOC in Table is valid at the EDR max times. Then use Figure to determine the corresponding SRF cf for each EDR max .…”
Section: The Edr Measurementsmentioning
confidence: 99%
“…The average values for the satellite parameters of Dist, TOC and R PC under the restriction of Dist ≤ 10.3 km were 6 AE 2 km (1r), 255 AE 11 Dobson Units (DU), and 27 AE 22%, respectively. These are typical values of TOC and R PC for the site (7,23,24).…”
Section: Resultsmentioning
confidence: 79%
“…An opposite diurnal cycle, with a peak shortly after local noon and a gradual decrease thereafter was reported by Kumar et al (2011). Silva (2013), have found no connection between the TOC diurnal variability and the aerosol load at three different sites. Antón et al (2010a) and Raj et al (2004) found that the observed diurnal TOC variations have different seasonal behaviour.…”
Section: Diurnal Toc Variationsmentioning
confidence: 84%
“…The diurnal variation of TOC has not been extensively investigated and in most studies it has been examined only for short periods during campaigns. In Table 6.1 (adopted from Silva, 2013) there is a summary of these studies. From Table 6.1 it is evident that diurnal variations in TOC, ranging from 4 to 40 DU have been detected by some Brewer spectrophotometers.…”
Section: Diurnal Toc Variationsmentioning
confidence: 99%